Synthesis and characterization of silver nanoparticles filled epoxy composite - Nurul Akma, Reduan (2018)
In this study, silver nanoparticles (AgNPs) were successfully synthesized via chemical reduction method. Silver nitrate (AgNO3), was used as a precursor, Sodium Borohydride (NaBH4) as a reducing agent and Cetyltrimethylammonium Bromide (CTAB) as a surfactant. The effect of reaction temperature, concentration of AgNO3 and NaCl were investigated in order to synthesize AgNPs with uniform shape and narrow particles distribution. The synthesized AgNPs was characterized by UV-VIS, TEM, XRD, and FESEM while; the average size was measured by Image-J software. XRD diffraction peak confirm that the samples prepared are AgNPs based on the peak position at 38.4° and 44.8°. Synthesis parameter at 60°C, 1.00 mM and 3.0 mM of reaction temperature, concentration of AgNO3 and NaCl respectively shows an optimum condition which produced AgNPs with narrow particle distribution, no agglomeration and uniform spherical shape at the end of reaction. The addition of NaCl affected the state of the reaction solution which is pH. This study shows solution at pH 7.5 gave better particles formation with no appearance of agglomerated particles. Meanwhile, stability study by UV-Vis and TEM analysis shows that the as-synthesized AgNPs was remain stable up to 1 month. The implementation of aqueous to organic phase transfer technique in this study is aimed to improve particles dispersivity in the epoxy polymeric system (composite preparation). FESEM analysis showed the AgNPs were dispersed well in the epoxy system. The composites of epoxy and AgNPs composite were fabricated as a function of particles concentration in the volume percentage (vol %) on thermal and thermo-mechanical properties of composite. Incorporation of AgNPs in the epoxy system is aimed to improve the thermal and thermo-mechanical properties of the resultant composite. The thermal and thermo-mechanical properties from TGA, DSC and DMA analysis shows that AgNPs- filled epoxy composite have higher thermal and thermo-mechanical properties compared to unfilled epoxy polymer. TGA analysis showed that, sample at 1.0 vol % AgNPs was recorded in the highest value of thermal properties compared to the unfilled AgNPs. From DMA analysis, samples at 0.2 vol% shows the thermo-mechanical properties of AgNPs-filled epoxy composite obtained 47-56% increment in the storage modulus and tan delta compared to unfilled AgNPs epoxy composite. Based on experimental results, thermal and thermo-mechanical can be conclude that AgNPs-filled epoxy composite can be used either in engineering or in various applications.